1987
DOI: 10.1073/pnas.84.2.424
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of thermodynamic efficiency of proton pumps on frequency of oscillatory concentration of ATP.

Abstract: In order to evaluate the utilization of variable ATP concentration produced by an oscillatory reaction (as in anaerobic glycolysis), we analyze the thermodynamic efficiency of power output of a cyclic, ATP-driven proton pump found in the plasma membrane of plant cells. The model used includes the coupling of potassium and calcium ion transport. Oscillations in the concentration of ATP can lead to either increases or decreases in efficiency compared to that at constant ATP concentration, with corresponding decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The efficiency of nuclear export is expected to be reduced if the RanGTP concentration decreases gradually on the cytoplasmic side of the NPC, even at a fixed ratio of nuclear and cytoplasmic RanGTP concentration. In addition, temporal changes in the rate of energy supply in the form of ATP or GTP might influence the efficiency of coupling (14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of nuclear export is expected to be reduced if the RanGTP concentration decreases gradually on the cytoplasmic side of the NPC, even at a fixed ratio of nuclear and cytoplasmic RanGTP concentration. In addition, temporal changes in the rate of energy supply in the form of ATP or GTP might influence the efficiency of coupling (14)(15)(16).…”
mentioning
confidence: 99%
“…To understand the mechanism of coupling, however, it is crucial to examine the process under in vivo conditions in which both the synergy of all (e.g., refs. 26 and 27) factors relevant for the export process and the natural flux rates of the reactions of the RanGTP cycle are preserved (14)(15)(16).…”
mentioning
confidence: 99%
“…Damped oscillatory behavior has been observed in an adenosine triphosphate (ATP)-driven proton pump (5). Ester hydrolysis by immobilized papain causes pH oscillations at the electrode upon which the papain is coated (6).Predictions have been made that the power output, the dissipation (for isothermal reactions, the product of AG and the rate) and hence the efficiency of nonlinear biochemical systems may be changed depending upon the mode of supply of reactants (steady or oscillatory) (7,8), with the same average consumption of reactants in either the oscillatory or steady mode ofsupply. We show experimentally that the mode of supply of reactants, steady or oscillatory, to a nonlinear, non-equilibrium biochemical reaction can determine the steady-state concentrations of the reaction.…”
mentioning
confidence: 99%
“…Previous studies have shown that phase shifting between the forces and fluxes in a driven nonlinear system may be responsible for efficiency changes (3,10,25). We have analyzed the phase relationship of AG1 (Eq.…”
Section: Proposed Experimental Systemmentioning
confidence: 99%